Communication And Classroom Management Strategies To Improve Student Personality Growth - Assahrawiza; Neviyarni S; Herman Nirwana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Classroom management refers to deliberate actions taken to overcome challenges and establish a conducive learning environment that facilitates the effective implementation of an educational curriculum. Achieving effective learning outcomes can be facilitated by fostering student motivation to consistently engage and actively participate in the learning process in class. To build an efficient learning environment, it is important to foster a sense of comfort, enjoyment, and motivation, which will serve as a catalyst and incentive for student learning. Therefore, achieving success in the student learning process requires the presence of capable teachers. To increase the effectiveness of classroom management and facilitate the learning process, it is very important for a teacher to actively engage in continuous reading to achieve comprehensive mastery of the subject matter. Additionally, teachers must have up-to-date knowledge, demonstrate unwavering dedication to their work, and be role models for their students.